Causal association between systemic lupus erythematosus and the risk of dementia: A Mendelian randomization study - Jin, Tianyu; Huang, Wei; Cao, Fangzheng; Yu, Xinyue; Guo, Shunyuan; Ying, Zhenhua; Xu, Chao (Frontiers in Immunology, 2022)
It is well-documented that systemic lupus erythematosus (SLE) is associated with dementia. However, the genetic causality of this association remains unclear. Mendelian randomization (MR) was used to investigate the potential causal relationship between SLE and dementia risk in the current study. We selected 45 single nucleotide polymorphisms (SNPs) associated with SLE from publicly available genome-wide association studies (GWAS). Summary level statistics were obtained from the dementia GWAS database. MR estimates were performed using the inverse variance weighted (IVW) method, MR-Egger method and weighted median (WM) method. Cochran’s Q test, the intercept of MR-Egger, MR-Pleiotropy Residual Sum and Outlier method, leave-one-out analysis and funnel plot were applied for sensitivity analyses. In the IVW method, no significant causal association was found between SLE and any type of dementia, including Alzheimer's disease, vascular dementia, frontotemporal dementia, and dementia with Lewy bodies. These findings were robust across several sensitivity analyses. Overall, our findings do not support a causal association between SLE and dementia risk.